Effect of language therapy alone for developmental language disorder in children: A meta-analysis - Fan, Shengfu; Ma, Bosen; Song, Xuan; Wang, Yuhong (Frontiers in Psychology, 2022)
Despite numerous studies on the treatment of developmental language disorder (DLD), the intervention effect has long been debated. Systematic reviews of the effect of language therapy alone are rare. This evidence-based study investigated the effect of language therapy alone for different expressive and receptive language levels in children with DLD. Publications in databases including PubMed, the Cochrane Library, the Wanfang Database and the China National Knowledge Infrastructure were searched. Randomized controlled trials were selected. The methodological quality of the included trials was assessed using the modified Jadad method. RevMan 5.3 software was used for the data analysis. Fifteen trials were included in this study. Compared with the control (no or delayed intervention) group, the intervention group showed significant differences in overall expressive language development (standard mean differences (SMD), 0.46; 95% confidence interval (CI), 0.12–0.80), mean length of utterances in a language sample (SMD, 2.16; 95% CI, 0.39–3.93), number of utterances in a language sample (SMD, 0.52; 95% CI , 0.21–0.84), parent reports of expressive phrase complexity (SMD, 1.24; 95% CI, 0.78–1.70), overall expressive vocabulary development (SMD, 0.43; 95% CI, 0.17–0.69) and different words used in a language sample (SMD, 0.62; 95% CI, 0.35–0.88). However, language therapy did not show satisfactory long-term effects on DLD. Although language therapy is helpful in improving the performance of children with DLD, its long-term effect is unsatisfactory.